The Effect of Ketamine on Depth of Hypnosis Indices During Total Intravenous Anesthesia – a Comparative Study Using a Novel Case Replay System - Stephanie S. Schüler (Hochschule für angewandte Wissenschaften Hamburg, 2019)
ntroduction: Processed electroencephalogram (pEEG) monitors provide clinical information by deriving a depth-of-hypnosis (DoH) index from the complex EEG signal. Ketamine, frequently used during surgery to reduce postoperative pain, is known to affect high frequency EEG power, particularly in the high beta and low gamma (24-32 Hz) range. Thus, DoH indices may become unreliable when ketamine is used. The purpose of this study was to compare the effects of ketamine on three commonly used DoH monitors by extending our EEG simulator to allow faithful replay of previously recorded EEG. Methods: Research Ethics Board approval was obtained for secondary use of EEG data from a randomized controlled trial of total intravenous anesthesia with ketamine, with three groups: Group 0.5 [receiving ketamine, 0.5 mg∙kg-1 bolus, 10 mcg∙kg-1∙min-1 infusion], Group 0.25 [receiving ketamine, 0.25 mg∙kg-1 bolus, 5 mcg∙kg-1∙min-1 infusion], and Control Group [no ketamine]. EEG data were replayed to three monitors: NeuroSENSE (NeuroWave Systems, DoH index = WAV), BIS (Medtronic, DoH index = BIS) and Entropy (GE Healthcare, DoH index = SE). Differences in DoH indices in the initial 15 min of case, during which peak ketamine DoH effect was expected to be observed, were presented as violin plots, in 30 second intervals, for the three devices. Furthermore, DoH differences between the each of the two ketamine groups and the control group were compared, in 5 minute intervals, using the Wilcoxon rank-sum test; similarly, differences between the monitors for each dosage group were explored. Finally, Bland-Altman analysis was used for pairwise comparison of agreement between the three DoH monitors. Results: Data were available for 27 cases. The presence of ketamine significantly increased the DoH index after induction of anesthesia for all three monitors. Compared to the control group, the median difference (MD) after induction, calculated over a one minute window, for Group 0.5 were 13.9, 16.0, and 15.5, for BIS, SE, and WAV respectively; similarly, MD for Group 0.25 were 13.3, 16.0, and 14.8, for BIS, SE, and WAV respectively (all p<0.025). Comparing the MDs between monitors within each dosage group, no significant differences were found in either ketamine group. The presence of ketamine did not alter the agreement between any pair of monitors. Conclusion: Regardless of the monitor used, the evaluated bolus doses of ketamine rendered the DoH indices temporarily unreliable. The observed DoH increase was likely caused by a power increase in the beta and gamma bands. However, there were no lasting significant differences between DoH in the three monitors, which is clinically reassuring.